Nine karyomorphs for spiny rats of the genus Proechimys (Echimyidae, Rodentia) from North and Central Brazil - Machado,Taís (2005)
Spiny rats of the genus Proechimys are morphologically diverse, widely distributed and have diploid numbers ranging from 2n = 14-16 to 2n = 62. In this paper we present cytogenetical data and brief comments on morphological and biogeographical issues related to spiny rats. In our sample of 42 spiny rats collected from 12 Brazilian Amazonian tropical rainforest and the Cerrado (Brazilian savanna) sites we detected nine karyological entities: four different karyomorphs with 2n = 30, three with 2n = 28, one with 2n = 15 and one with 2n = 44. Based on qualitative morphological characters these karyomorphs can be allocated to five species within the goeldii, guyannensis and longicaudatus species groups.